Legal and ethical issues in ART "outcomes" research - Nelson, Erin L (Health law journal, 2005)
In the almost 30 years since the birth of the first "test-tube baby,"6 the science around reproductive and genetic technologies has exploded, giving rise to new tests and technological breakthroughs on a routine basis. Preimplantation genetic diagnosis (PGD), for example, permits scientists to diagnose genetic conditions in an in vitro embryo,7 prior to it being implanted in a woman's uterus through in vitro fertilization (IVF), a technology in which an ovum is fertilized with a sperm cell outside the woman's body.8 And if IVF alone will not suffice to assist a couple to conceive, because of very low sperm count or immotile sperm, a procedure termed intra-cytoplasmic sperm injection (ICSI) might be appropriate - a single sperm cell can be injected directly into the ovum to ensure that fertilization takes place.9 Other variations on the IVF theme include a procedure called in vitro maturation (or IVM), in which immature oocytes are matured in vitro for 24-48 hours, eliminating the need for risky hormonal stimulation of the ovaries prior to harvesting eggs,10 and IVF with blastocyst embryo transfer, which involves waiting for five to six days post-fertilization to transfer the embryo(s) to the woman's uterus, which, it is hoped, will lead to a greater likelihood of implantation." Reproductive cloning, perhaps the most 'high tech' of the new reproductive technologies (and certainly the most controversial), allegedly looms on the horizon as well.12 Consent, or more particularly, informed consent, is a cornerstone of legal and ethical governance of health research.33 In order to satisfy legal and ethical requirements, researchers must obtain the "free and informed consent"34 of each participant. Legally and ethically valid consent to participation in research must be voluntary (given without undue influence, manipulation or coercion35), it must be given by a person competent to provide it,36 and it must be "informed." In the clinical practice context, the law holds that an informed patient is one who has been apprised of all "material, special or unusual risks" related to the proposed therapeutic intervention.37 In the health research context, particularly where the research is not of intended benefit to the participants, the courts have held researchers to a higher standard of disclosure, that of "full disclosure" of all risks: rare, remote or potential.38 Canadian ethics policy also demands that the researcher provide prospective subjects (or authorized third parties) with "full and frank disclosure of all information relevant to free and informed consent."39 While it is settled law that parents may provide consent to their child's participation in research of potential benefit,67 there exists real doubt about parental authority to consent to their child's participation in 'non-beneficial' research,68 and particular concerns have been raised in the context of genetic research.69 Parents' authority to consent to their child's participation in research stems from their authority to consent to their child's medical care, but here (as in the treatment context), the parents' decision must be consistent with the child's best interests.70 The clear implication, in the clinical setting, of a particular intervention being recommended, is that it is in the best interests of the child to undergo the procedure or treatment in question. In the case of participation in health research, the picture becomes clouded.